PENGARUH KEAHLIAN KEUANGAN KOMITE AUDIT DAN MANAJEMEN LABA TERHADAP AUDIT REPORT LAG - Aan Andrianingsih; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2023)
Audit report lag is important because it can affect the timeliness of accounting information used by internal and external users for their decision making. This is the motivation for this research to be conducted, so this study aims to distinguish the effect of audit committee financial expertise and earnings management on audit report lag. The dependent variable in this study is audit report lag and there are two independent variables in this study, namely the financial expertise of the audit committee and earnings management. Financial expertise is measured by the proportion of the number of audit committee members who have a background or experience in accounting or finance. Earnings management is measured by Discretionary Accrual with the additional variable Return on Assets (ROA). Audit report lag is measured by the number of days between the end of the fiscal year and the audit report signature date (natural log).This research is quantitative research. The population in this study are mining companies listed on the Indonesia Stock Exchange from 2017 to 2021. Sampling used a purposive sampling technique. The number of samples used was 184 (one hundred and eighty-four). The data collection method in this study is collection. The data analysis technique used in this study is descriptive statistics, classic assumption test, multiple linear regression analysis using SPSS version 25.The results of this study indicate that partially (1) financial expertise has a significant negative effect on audit report lag, which means that the more audit committees with financial expertise, the shorter or decreased the audit report lag. (2) Earnings management has a negative effect on audit report lag, this means that the higher the earnings management, the lower or shorter the audit report lag. Then simultaneously the expertise of the financial audit committee and earnings management both have a significant effect on the delay in the audit report.